Factors Affecting Parents' Acceptance towards Children with Familial Intellectual Disability (ID) - Elsa Gusrianti; Tri Indah Winarni; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2018)
Background: Familial intellectual disability (ID) is a condition where two or more family members are affected ID, which may influence the whole family well-being. Children with intellectual disability often receive negative response from the society, which may trigger different reactions from the parents, such as denial or neglect of their child. Besides, most parents give more attention and provide the best care for their children. Factors that may influence parents’ acceptance towards children with familial ID are social support, religious coping, supporting facilities, family income, education, mothers’s age, and other significant factors.Objective: This study was aimed to analyze factors that affect parents’ acceptance towards children with familial intellectual disabilities (ID).Methods: This was an analytic observational study with cross sectional approach. Data were collected using interview with 20 mothers of familial intellectually disabled children including demographic data, pedigree construction, using Parental Rejection Questionnaire (PARQ), Brief Arab Religious Coping Scale (BARCS), Social Support Questionnaire Short Form (SSQSR) and Supporting Facilities Questionnaires. Data was analyzed using multivariate logistic regression.Results: Parents’ acceptance was significantly affect by social support (p<0.05), while religious coping, supporting facilities, family income, education, and mothers’s age did not significantly influence parents’ acceptance (p >0.05).Conclusion: Social support has influenced parent’s acceptance of their familial ID Children